Human library dalam membangun lingkungan inklusif: Layanan living collection Perpustakaan UIN Sunan Kalijaga - Ghalib Muhammad Syukri Al Ghiffary; Anis Masruri; Shinta Dewi (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This research aims to analyze human libraries in building an inclusive environment with a focus on a living collection case study at the UIN Sunan Kalijaga library. Qualitative and descriptive research methods were used. Data were collected through observations, interviews, and a literature study. The results show that users are aware of the existence of living collections through user education activities and part-time experience programs. There are two factors that encourage users to access residential collections: internal and external. The internal factors that influence users to utilize live collections are curiosity and curiosity. External factors that influence users to utilize residential collections for research purposes. There is a Living collection Program that has a positive impact as a figure that inspires users. Procedurally, there were no significant barriers to accessing the living collections.